DigestAR: Android Based Augmented Reality Application for IPAS Digestive System Learning with the Fisher Yates Algorithm - Muhammad Hasan Fikri; Febrian Dewanto; Nur Latifah Dwi Mutiara Sari (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2026)
The teaching of Natural and Social Sciences (IPAS) regarding the human digestive system in elementary schools still largely relies on two-dimensional media, causing students to struggle with understanding the concrete forms and functions of digestive organs. The purpose of this study is to develop an Android-based learning application called DigestAR that integrates Augmented Reality (AR) technology and Kuis (quiz) features to support the learning process for material on the human digestive system. The Multimedia Development Life Cycle (MDLC) approach was used to create the application, which in this study was limited to the testing phase, encompassing concept, design, content collection, assembly, and testing. The application was built using Unity with the C# programming language, the Vuforia SDK to support AR features, and the Fisher Yates algorithm to randomly shuffle quiz question order evenly, ensuring a different sequence in each session. The application’s main features include 3D visualizations of digestive organs, learning materials, and evaluation quiz. System testing involved Black Box Testing, White Box Testing, and User Acceptance Testing (UAT). The test results showed that all application functions operated as intended. The UAT results, which involved students and teachers at SDN Karangtempel in Semarang, as well as university students, yielded an average score of 96.67%, categorized as “very good.” These results indicate that the developed application has a high level of user acceptance and can serve as an alternative interactive learning medium to aid students’ understanding of the human digestive system.